HEK222 - Critical Reading And Writing June 2019 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (Universiti Sains Malaysia, 2019)
Second Semester Examination 2018/2019 Academic Session June 2019 HEK222 -Critical Reading And Writing Duration : 3 hours